A Study of the Relationship Between Iranian EFL Learners’ Multiple Intelligences and their Performance on Writing - Ahmadian, Moussa; Hosseini, Samaneh (Mediterranean Journal of Social Sciences, 2012)
The Multiple Intelligences Theory (MIT), proposed by Gardner (1983), claims that there are at least eight differenthuman intelligences. This new view of intelligence with emphasis on learner variable has been used in language learning andteaching settings. The theory stresses that if individual differences are taken into account and classroom activities arediversified, language learners can better improve their language skills. The present study investigates possible relationshipbetween L2 learners’ multiple intelligence (MI) and their writing performance. Thirty three female homogeneous Persianspeaking EFL learners participated in the study. The instruments used were the Multiple Intelligence Developmental AssessmentScales (MIDAS), an instrument designed by Shearer in 1996, and the participants' average scores on two writing tasks, as anindex of writing products. The correlational analysis of the results revealed a statistically significant relationship betweenparticipants' MI and their performance on writing. Furthermore, the results of regression analysis showed that among all eightintelligences, linguistic intelligence is the best predictor of writing performance. The findings suggest English teachers toconsider the role of MI in classes and provide more effective activities to help students improve second language writing ability.Possible implications of the findings for language teaching and teaching writing have been discussed.